JURNALIS PEREMPUAN DAN CITIZEN JURNALISM - Nurul Qomariah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
Undeniable, that the amount of women journalist in printed media or electronic media is very limited in comparison with men journalist. As a result, more women only become news sources to a media. This article discuss why does the amount of women journalist is very limited and what the alternative that can be done to push women more active as journalist. From the analysis that have been done, it founf that the cause of the limited amount of women journalist is more women do not understand the benefit of writing to her self and women have limited time to pour her mind in writing, although she is anxious to write. The limitation of women journalist can be overcome throuh te citizen of journalism.